From Teachers’ to Schools’ ICT Competence Profiles - Sergis, S.; Sampson, Demetrios (2014)
It is widely accepted that schools have not fully exploited the advantages of information and communication technologies (ICT) as an enabler of improved learning and teaching practices despite the several initiatives targeting that issue. The reasons for this are multifaceted and include, among others, staff competences, financial issues, infrastructure-related shortcomings and culture factors. This complexity in approaching the problem is attributed to the fact that schools are, in themselves, a wide ecosystem of interrelating (f)actors. Deriving from this, the need for a method to effectively capture all these factors and their level of contribution to the overall schools’ ICT uptake is essential. Towards that end, this chapter aims to investigate and outline a framework for profiling schools’ ICT competences, which extends the current eMaturity implementations and, building on the concept of organizational competence, incorporates additional elements to be considered. The proposed approach could lead not only to a better understanding of the current technological status of schools, but, also, to more informed decisions regarding their potential corrective paths in the areas identified as flailing.